Pengetahuan Dan Sikap Ibu Dengan Keikutsertaan Dalam Kelas Senam Hamil Di Rumah Sakit Colombia Asia - Mardha, Muthia Sari; Panjaitan, Ivan Sri Marsaulina (Window of Health : Jurnal Kesehatan, 2020)
The disobedience of mother following the class activities of pregnant is one of the obstacles in implementing classroom activities for pregnant that will have a global impact on the health. The purpose of this study was to determine the relationship between the knowledge and the participation mother in pregnancy classes, and the relationship between the attitude and the participation mother in pregnancy classes. This type of research is analytical survey research with a cross-sectional. The population in this study were all pregnant women trimester 3 who visited at Hospital Colombia Asia totaling 103 people. The sample in this study was 82 people with accidental sampling. Research instrument using a statement questionnaire. The test used in this study is the chi-square test with alpha 0.05. The statistical test results of the relationship between the knowledge with the participation mother in the pregnancy class obtained a value (p-value) = 0.019 <Î± 0.05, which means there is a relationship between knowledge and the participation of mother pregnancy classes. The relationship of cross-tabulation between the attitudes and the participation mother in the pregnancy class obtained a value (p-value) = 0.029 <Î± 0.05, which means there is a relationship between the attitude with the participation mother in pregnancy classes. The conclusion is that there is a relationship between the knowledge and the participation mother in pregnancy classes and there is a relationship between the attitude and the participation mother in the pregnancy class.